Mediating influence of job burnout and job satisfaction in relationship between work stress and organizational commitment among exceptional education teachers in Baghdad, Iraq - Mohammad Bashir Hassan AlDabi; Hajar Torkan; Abbas Ali Shallal; Ali Mehdad (طب کار)
Introduction: Educators in exceptional schools represent a significant research focus explored by researchers across various disciplines, primarily owing to the intense demands of their jobs and their coping strategies for such circumstances. In light of this, the present research was conducted to explore the connection between job stress and organizational commitment, focusing on the mediating effects of job satisfaction and job burnout among exceptional education teachers in Baghdad, Iraq. Materials and Methods: The method of research employed was causal correlation research (structural equation modeling). The statistical population for the research consisted of all the exceptional education teachers from elementary schools in Baghdad, Iraq, during the spring and summer of 2024, totaling 524 individuals. Among them, 200 individuals (100 females and 100 male) were chosen as samples using the convenience sampling method. Data were collected using occupational stress questionnaires of the Health and Safety Institute of England (HSE), job burnout by Maslach, & Jackson (1996), organizational commitment by Allen and Meyer (1991), and job satisfaction evaluation by Smith et al. (1969). To analyze data, a structural equation model was used through SPSS 26 and AMOS 23 software. Results: The results of direct effects showed that job stress significantly impacted organizational commitment, job satisfaction, and burnout (p<0.01). Additionally, both job satisfaction and job burnout significantly influenced organizational commitment (p<0.01). Examining the indirect effects revealed that both job satisfaction and job burnout played a significant mediating role in  how work stress influences organizational commitment (p<0.01). Conclusion: According to the results of this study, it is recommended that managers and policymakers in the Iraqi education system focus significantly on decreasing job stress, due to its impact on enhancing job satisfaction, fostering organizational commitment, and lowering job burnout among special education teachers. In this regard, they can take advantage of the presence and advice of organizational psychologists to recognize and address the sources of job-related stress